2016
DOI: 10.32771/inajog.v36i4.322
|View full text |Cite
|
Sign up to set email alerts
|

Placental Growth Factor Level is Lower in Early-Onset Preeclampsia, while Tumor Necrosis Factor Alpha Level does not Show any Difference between Early and Late Onset Preeclampsia

Abstract: Objective: To analyze the difference of PlGF and TNF-α serum level between early-onset and late-onset preeclampsia. Method: This is a cross-sectional analytic comparative study comparing serum level of PlGF and TNF-α between groups with earlyand late-onset preeclampsia. Each group consists of 32 subjects who met inclusion criteria and presented to Dr. Hasan Sadikin Hospital or its district hospitals in September - November 2012. Statistical analysis was performed with Kolmogorov Smirnov test, Saph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Conclusions from several studies on antiangiogenic and angiogenic biomarkers by Villa, et al (2013) andRahmiLaila, et al (2016) regarding sFlt-1, is that serum levels of sFlt-1 in early onset PE are higher than late onset PE. The results of the study by Akbar, et al, (2017) found that soluble endoglin (sEng) serum levels were significantly higher in early onset PE compared to late onset PE (47.65 ± 40.17 vs 13.46 ± 9.48), while the mean serum PIGF in the early onset PE group (53.03 ± 38.07 pg / mL) was lower than late onset PE (241.80 ± 192.83 pg / mL) with p <0.0001 (Ekapatria, et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Conclusions from several studies on antiangiogenic and angiogenic biomarkers by Villa, et al (2013) andRahmiLaila, et al (2016) regarding sFlt-1, is that serum levels of sFlt-1 in early onset PE are higher than late onset PE. The results of the study by Akbar, et al, (2017) found that soluble endoglin (sEng) serum levels were significantly higher in early onset PE compared to late onset PE (47.65 ± 40.17 vs 13.46 ± 9.48), while the mean serum PIGF in the early onset PE group (53.03 ± 38.07 pg / mL) was lower than late onset PE (241.80 ± 192.83 pg / mL) with p <0.0001 (Ekapatria, et al, 2012).…”
Section: Introductionmentioning
confidence: 99%